2022
DOI: 10.1111/1759-7714.14599
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of the combination of preoperative SUVmax and CEA in patients with clinical stage IA lung adenocarcinoma

Abstract: Background Preoperative maximum standardized uptake value (SUVmax) of 2‐[18F]‐fluoro‐2‐deoxy‐D‐glucose positron emission tomography and serum carcinoembryonic antigen (CEA) have been reported as prognostic factors for lung adenocarcinoma. However, the significance of combined SUVmax and CEA in early‐stage lung adenocarcinoma is not well known. Methods We retrospectively evaluated the relationship between the combination of SUVmax and CEA and the prognosis of 410 patients with clinical stage IA lung adenocarcin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Hashinokuchi et al even studied the combination of preoperative maximum standardised uptake value (SUVmax, cut-off values: 2.96) and CEA (cut-off values: 5.3 ng/mL) on the prognosis of stage IA LUAD. The survival time of patients with higher SC (SUVmax and CEA) levels was significantly reduced compared to patients with lower levels [ 138 ]. Regarding the predictive effects of postoperative CEA, serum elevated CEA was the significant determinant for worsening prognosis in stage I NSCLC [ 139 , 140 , 141 , 142 ].…”
Section: Resultsmentioning
confidence: 99%
“…Hashinokuchi et al even studied the combination of preoperative maximum standardised uptake value (SUVmax, cut-off values: 2.96) and CEA (cut-off values: 5.3 ng/mL) on the prognosis of stage IA LUAD. The survival time of patients with higher SC (SUVmax and CEA) levels was significantly reduced compared to patients with lower levels [ 138 ]. Regarding the predictive effects of postoperative CEA, serum elevated CEA was the significant determinant for worsening prognosis in stage I NSCLC [ 139 , 140 , 141 , 142 ].…”
Section: Resultsmentioning
confidence: 99%
“…The sensitivity of one of these indicators applied alone is 0.30–0.50, and the specificity is 0.45–0.70. The sensitivity and specificity of the combined application of these indexes were ∼0.85 and 0.80 12 . In our literature search, they have not been used in MPLC and SPLC, lung cancer IM studies.…”
Section: Discussionmentioning
confidence: 98%
“…CEA, a serum glycoprotein, is the most widely used biomarker of colorectal, breast, and lung cancer ( 43 ). In our study, we found that high serum CEA levels were related to negative PD-L1 expression, which was consistent with the results of Kato et al ( 26 ); however, they did not verify the efficiency of CEA in evaluating PD-L1 positive expression, nor did they identify its optimal cut-off value.…”
Section: Discussionmentioning
confidence: 99%